Surface subsidence associated with abandoned mine workings in the Goldenville mining district, Nova Scotia - Hill, J.; Maddison, L.; Kavanaugh, C. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1997)
Mining in Meguma gold districts has resulted in the development of hundreds and possibly thousands of underground stopes since gold was first discovered in 1861. These stopes are on the order of 1 to 2 m wide and extend up to hundreds of metres along strike and tens of metres in height. Many are open or partially filled and capped by surface crown pillars of quartz and phyllite that are as little as 2 m thick vertically. The majority of these stopes have been abandoned for more than fifty years and the long term stability of their surface crown pillars is uncertain. Rock mass behaviour and surface subsidence have been monitored in part of the Goldenville mining district since 1991. Surface subsidence basins have increased in both number and depth during this period. Stope locations and the nature of crown pillars above the stopes are poorly defined due to lack of accurate mining records and the presence of overburden. Furthermore, some of the subsidence features in the area are obviously related to the failure of overburden plugs rather than bedrock caps. For these reasons, a causal relationship between surface crown pillar failure and the surface subsidence features currently existing in the Goldenville district cannot be established at this time. However, time domain reflectometry and structural data suggest that the near-surface rock mass between and above abandoned stopes is undergoing progressive degradation by gravity-induced failure of slab-like blocks along intersecting and closely-spaced bedding, cleavage and joint surfaces. Uncertainties in factors such as rock mass quality, crown pillar dimensions and water table fluctuations make it impossible to predict when and where crown pillars might fail. However, failure of the weaker crown pillars and consequent surface subsidence are inevitable if these rock mass movements continue indefinitely.